Marketing Strategy Analysis To Increase Visitors To Solo Paragon Lifestyle Mall - Bita Veny Pratiwi; Sigit, Murwanto (SEAN Institute, 2024)
Solo, an important economic center in Central Java, is experiencing rapid growth, especially in the trade and services sector. Solo Paragon Lifestyle Mall, as a leading shopping center, needs an effective marketing strategy to compete. Through events and promotions, the mall can attract visitors to come to Solo Paragon so as to generate a crowd that will bring buyers for tenants and improve the brand image of Solo Paragon Lifestyle Mall. In this study, the author aims to analyze marketing strategies to increase Solo Paragon Lifestyle Mall visitors. The method that the author uses is qualitative with data collection techniques of in-depth observation and internship participation action. The intended unit of analysis in this research is the Marketing Communication team at Solo Paragon Lifestyle Mall. The unit of analysis that will be studied is the 4P marketing strategy mix (Product, Price, Place, Promotion) carried out by the Marketing Communication team to increase visitors at Solo Paragon Lifestyle Mall. In addition, it is also a SWOT analysis to find out the advantages and disadvantages of Solo Paragon Lifestyle Mall.